High-efficiency piezoelectric micro harvester for collecting low-frequency mechanical energy. (7th November 2016) - Li, Xin; Song, Jinhui; Feng, Shuanglong; Xie, Xiong; Li, Zhenhu; Wang, Liang; Pu, Yayun; Soh, Ai Kah; Shen, Jun; Lu, Wenqiang; Liu, Shuangyi
Abstract: A single-layer zinc oxide (ZnO) nanorod array-based micro energy harvester was designed and integrated with a piezoelectric metacapacitor. The device presents outstanding low-frequency (1–10 Hz) mechanical energy harvesting capabilities. When compared with conventional pristine ZnO nanostructured piezoelectric harvesters or generators, both open-circuit potential and short-circuit current are significantly enhanced (up to 3.1 V and 124 nA cm −2 ) for a single mechanical knock (∼34 kPa). Higher electromechanical conversion efficiency (1.3 pC/Pa) is also observed. The results indicate that the integration of the piezoelectric metacapacitor is a crucial factor for improving the low-frequency energy harvesting performance. A double piezoelectric-driven mechanism is proposed to explain current higher output power, in which the metacapacitor plays the multiple roles of charge pumping, storing and transferring. An as-fabricated prototype device for lighting an LED demonstrates high power transference capability, with over 95% transference efficiency to the external load.